Analysis Of The Influence Of Servicescape On Burnout Levels Of Private Sector Employees In Bengkulu - Sandy Muhammadiansyah; Nafri Yanti (Jurnal Fokus Manajemen, 2026)
The purpose of this study is to analyze the influence of servicescape on the level of burnout of private sector employees in Bengkulu Province. This study involved respondents from various service and industrial sectors, with a total of 102 respondents. Data were analyzed using linear regression and then processed using the IBM SPSS Statistics 25 application. Based on the results of the study, it is known that two servicescape variables, namely ambient conditions and exterior facilities, have a significant influence on burnout of private sector employees. Meanwhile, two other servicescape variables, namely spatial layout & functionality, and signs, symbols & artifacts, do not have a significant influence. This study confirms that physical environmental factors in the workplace, especially environmental conditions and exterior facilities, play an important role in influencing the level of burnout experienced by private sector employees. Therefore, companies operating in Bengkulu should consider investing in improving work facilities in order to help improve the physical and mental well-being of employees, as well as reduce excessive stress.